Magnetic resonance imaging diagnosis of Mayer-Rokitansky-Kuster-Hauser syndrome - M J Govindarajan; Revathi S Rajan; Arjun Kalyanpur; Ravikumar (Wolters Kluwer Medknow Publications, 2008)
Magnetic resonance imaging (MRI) is the mainstay in the imaging evaluation of Mullerian agenesis, but is not routinely being utilized, particularly in India. Though sagittal MRI clearly demonstrates the absence or hypoplasia of the uterus and the axial images demonstrate the normal ovaries, it is the ability to identify and objectively evaluate other associated anomalies that makes MRI a unique diagnostic modality. It is also noninvasive and has multiplanar capabilities at the same time having a very high soft tissue resolution. We presume it can be used as a comprehensive imaging package for evaluating these patients at one sitting. We report a case of Mullarian agenesis presenting as primary amenorrhea stressing the role and benefits of MRI.